Study of Yang's Onion Flap Technique for Release of Scarred Eponychium and Nail Fold Reconstruction in Burn Patients - Srivastava, Vaishali; Sharma, Upendra; Rathore, Deepak (Indian Journal of Plastic Surgery, 2022)
Background Abnormalities of fingernail growth and appearance are among the most common deformities encountered after burn injury to the hand. Various techniques used for resurfacing defects include incision of the scarred eponychium and advancement of the distal segment, flap reconstruction-distally, and proximally based transposition/advancement flaps, composite graft techniques, microvascular transfer. In the present study, we used an onion flap to release scarred eponychium and nail fold reconstruction in a single stage without using soft tissue from another area.Materials and methods Forty-four burnt fingers were operated using Yang's onion flap technique. Patients were assessed for flap necrosis, hematoma and infection in the early postoperative period and for donor site scar, nail appearance, and symptomatic relief in a follow-up for at least 4 months.Results The flap was successfully performed on all fingers. Only two fingers had flap necrosis. There was no incidence of hematoma or infection. The donor site scar and nail plate appearance improved and was acceptable to most patients after surgery. There was also significant relief in daily activities in 19 out of 28 symptomatic patients.Conclusion Yang's flap to correct nail deformities in burn patients is feasible in Indian scenario. It is associated with a low complication rate and improved nail appearance. There is also significant symptomatic relief in performing daily activities after surgery.
Keywords: onion flap; post-burn nail deformity; nail fold reconstruction